Samoson Ratsaranrom (Khana Ratsadons Office): A Neglected Urban Heritage of the Peoples Party - Koompong Noobanjong (My University, 2022)
Current architectural scholarship in Thailand has witnessed a renewal of interest in built forms commissioned by the People’s Party, a group of civil servants and military officers known in Thai as Khana Ratsadon that overthrew the absolute monarchy in 1932. Despite an increasing number of publications on the arts and architecture of the People’s Party, its office in Bangkok remains largely absent from those investigations and public recognition. As such, this research presents a multidimensional inquiry to better understand the role of Samoson Ratsaranrom in Thai society. Once functioning as Khana Ratsadon’s office, the building was examined in terms of: (1) means for power mediation; (2) reflection of the ideological views of the People’s Party; and (3) expression of the modern Thai identity. Via discourse and iconographical analyses, the study revealed that apart from serving as a material manifestation of the revolutionary spirit and ideology, this modest structure acted as a social space for interactions between people through festivities, namely the annual constitutional fairs. Standing unassumingly in Saranrom Royal Garden–which has become a public park nowadays–the building was an integral part of the cultural practices during the early days of the post-absolutist regime. Owing to the said historical importance, a proposition could be put forward that not only should Khana Ratsadon’s office be incorporated into DOCOMOMO Thailand’s inventory, but also be registered as a national treasure by the Fine Arts Department. In addition, critical examination of this Modernist structure begged a question as to whether the academic obscurity of the building was indicative of attempts to erase the cultural legacies the People’s Party by the Thai state, which had been subtly implemented for decades. Regardless of the answer, recent destruction and disappearance of the cultural heritages left behind by the People’s Party make the preservation of Samoson Ratsaranrom even more urgent.
Keywords: Treasure; Southeast Asian Sociopolitical Studies